Views of conservation volunteers and environmental specialists on genetic technologies for pest control in Aotearoa New Zealand - Mercier, Ocean Ripeka; Jones, Natalie; King Hunt, Alan; Hemmerling, Liam; MacDonald, Liliana; Horowitz, Joseph; Kanli, Rafaela; Palmer, Symon; Belcher, Sara; Lester, Philip J. (Frontiers in Conservation Science, 2024)
Pests such as invasive exotic wasps and rats are a serious threat to Aotearoa New Zealand’s native species, and the country has been working toward the New Zealand government’s target of eliminating rats, possums, and mustelids by 2050. Since current control methods lack the efficiency and scalability to eradicate mammalian predators and pest invertebrates like wasps, gene technologies are being considered and developed as additional methods of control. Social studies to gauge public perceptions on these novel technologies have also been conducted, with a strong emphasis on Indigenous viewpoints and the importance of societal compacts, particularly Te Tiriti o Waitangi (Treaty of Waitangi). Conservation volunteers and environmental specialists are uniquely experienced and positioned to inform decisions on which technologies are developed and how, but 1) what are their views on genetic technologies for pest control and 2) how do they expect gene technology for pest control to be discussed and developed? To help answer these two questions, we conducted a new analysis of a dataset of 8,199 nationwide survey responses, 23 in-depth surveys of wasp control volunteers, and 18 interviews with rat and wasp control volunteers and environmental experts, using Q-methodology. All of the conservation volunteers, scientists, academics, and environmental professionals expect that risks associated with the technology are carefully and fully identified and mitigated against. A majority cautiously supports gene technologies for their potential to more effectively control pests. A significant minority supports gene technologies for pest control under certain conditions, most significantly if Māori as Tiriti partners are also supportive. A smaller minority has doubts and concerns about gene technologies for pest control and raises important considerations for scientists and policy-makers alike. Addressing all of these concerns, supported by Tiriti-based decision-making processes, will facilitate consensus-based discussions and decisions on genetic technology use.